PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM VISUALISASI DAN INOVASI PRODUK KULINER: DAMPAKNYA TERHADAP PERSEPSI DAN PREFERENSI KONSUMEN - Jaya, Unggul Putra (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
The advancement of Artificial Intelligence (AI) has significantly transformed the culinary industry, particularly in food visualization and product innovation. Visual aesthetics play a crucial role in shaping consumer perceptions and influencing purchase decisions. This study investigates how AI-generated food imagery affects consumer perceptions of quality and purchase intention, and explores consumer responses to AI- assisted culinary product innovations. The research employs a quantitative experimental method with an A/B test design, comparing consumer reactions to AI-generated food images and authentic food photographs without disclosing their sources. Additionally, a consumer survey evaluates perceptions of AI-driven culinary innovations. Findings indicate that AI-generated visuals significantly enhance perceived product quality and attractiveness. However, when consumers are aware that the visuals are AI-generated, purchase intention decreases due to concerns over product authenticity. Despite this, consumers express interest in culinary innovations resulting from human-AI collaboration, provided product safety and authenticity are maintained.